2022
DOI: 10.2298/gsgd2202067i
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of flooded areas in the lower part of the Sana river basin (Bosnia and Herzegovina)

Abstract: Floods are the most frequent and devastating natural hazard event in Bosnia and Herzegovina. The detected increase in extreme precipitation over the study area in the last period has altered flood event patterns due to climate changes. Higher frequency of flood events and lack of flood protection infrastructure has a severe impact on socio-economic sectors and natural ecosystems. This paper focuses on the identification of flooded areas for each single flooding event in the lower part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…As part of this research, thanks to CHIRPS data, the occurrence of extreme precipitation was observed three years in a row (2017, 2018 and 2019). In addition to extreme precipitation, in the area of the SRB, Ivanišević et al (2022) established the number of days with higher water levels (2018 and 2019) that exceeded the emergency f lood protection elevation. The presented results indicate the regulari-ty of the occurrence of extreme precipitation, which leads to higher water levels, and the cause-and-effect occurrence of f loods.…”
Section: Discussionmentioning
confidence: 99%
“…As part of this research, thanks to CHIRPS data, the occurrence of extreme precipitation was observed three years in a row (2017, 2018 and 2019). In addition to extreme precipitation, in the area of the SRB, Ivanišević et al (2022) established the number of days with higher water levels (2018 and 2019) that exceeded the emergency f lood protection elevation. The presented results indicate the regulari-ty of the occurrence of extreme precipitation, which leads to higher water levels, and the cause-and-effect occurrence of f loods.…”
Section: Discussionmentioning
confidence: 99%